AN ANALYSIS OF METAL SURFACE IMMERSED IN BASED LUBRICANT FROM MINERAL OIL CONTAINING VEGETABLE OIL WITH RICE BRAN OIL BASED BIO-INHIBITOR - Nugrahani, Ratri Ariatmi; Hendrawati, Tri Yuni; Susanty, Susanty (Jurnal Bahan Alam Terbarukan, 2018)
The need for environmentally friendly chemical products in daily needs encourages the production of its. The green-chemistry concept is using the process and produces chemical products that are ecofriendly. Including ecofriendly chemical products are base oil and additives for lubricants, grease, and fuels. The production is expected to reduce the consumption of mineral and synthetic base oils, so it will be biodegradable and renewable. This study compares the results of analysis of metallic surfaces immersed in the mixture of mineral and vegetable base oil, with the addition of rice bran oil bioadditive, ie epoxidized methyl ester (EME) and hydroxyl alkylbenzene sulphonic acid ester (HASE). The research method consists of preparing HASE; analyzing the effect of HASE and EME bioadditives addition on the mixture of base oil to the changing of metallic weight immersed in the mixture; determining the inhibition efficiency of the EME and HSAE additions; analyzing the metal surface using SEM-EDX (Scanning Electron Microscope) / (Energy Dispersive X-ray Spectrometry) to find images of microstructure and chemical compounds contained in specimens, and testing the metal difractogram immersed in base oil mixtures with bioadditive using XRD (X-Ray Diffraction). SEM test results of carbon steel immersed in a mixture of base oil and bioadditives show corrosion in which the metal surface color immersed in EME bioadditive mixtures is brighter. EDX spectra of metal sample surfaces immersed in a mixture of base oil, EME and HASE contain carbon (C) and iron (Fe). The carbon content in carbon steel samples immersed in the mixtures and HASE is higher. XRD test results show Fe2O3 phases in carbon steel samples immersed in the HASE bioadditive mixture are higher than in EME. While Fe3O4 phases in carbon steel samples immersed in the EME bioadditive mixture are higher than Fe2O3 phases in samples immersed in HASE bioadditive mixture.